QMX: A versatile environment for hybrid calculations applied to the grafting of Al2Cl3Me3 on a silica surface. Issue 13 (23rd January 2013) - Kerber, Torsten; Kerber, Rachel Nathaniel; Rozanska, Xavier; Sautet, Philippe; Fleurat‐Lessard, Paul
Abstract We present a new software to easily perform QM:MM and QM:QM' calculations called QMX. It follows the subtraction scheme and it is implemented in the Atomic Simulation Environment (ASE). Special attention is paid to couple molecular calculations with periodic boundaries approaches. QMX inherits the flexibility and versatility of the ASE package: any combination of methods namely force field, semiempirical, first principle, and ab initio, can be used as hybrid potential energy surface (PES). Its ease of use is demonstrated by considering the adsorption of Al2Cl3Me3 on silica surface and by combining different levels of theory (from standard DFT to MP2 calculations) for the so‐called High Level cluster with standard PW91 density functional theory calculations for the Low Level environment. It is shown that the High Level cluster must contain the silanol group close to the aluminum atoms. The bridging adsorption is favored by 58 kJ mol−1 at the MP2:PW91 level with respect to the terminal position. Using large clusters at the MP2:PW91 level, it is shown that PW91 calculations are sufficient for structure optimization but that embedded methods are required for accurate energy profiles. © 2013 Wiley Periodicals, Inc.